P273 Association of incident pneumonia and exacerbations with extrafine triple therapy in one single inhaler in copd patients: a post-hoc analysis from trilogy and trinity studies. (15th November 2017) - Scuri, M; Vestbo, J; Papi, A; Corradi, M; Spinola, M; Montagna, I; Francisco, C; Cohuet, G; Vezzoli, S; Muraro, A; Petruzzelli, S; Singh, D
Abstract : Rationale: Efficacy and safety of extrafine fixed triple combination of beclometasone dipropionate, formoterol fumarate, and glycopyrronium bromide (BDP/FF/GB; 100/6/12.5 mcg, two actuations BID via pMDI; 'fixed triple') has been recently demonstrated in two phase III trials. Fixed triple has shown superiority in improving lung function and reducing moderate/severe exacerbations versus BDP/FF (Fostair 100/6 mcg, two actuations BID via pMD; TRILOGY – Singh et al. Lancet 2016; 388: 963–73) and versus tiotropium (18 mcg one inhalation OD via DPI; TRINITY – Vestbo et al. Lancet 2017; 389: 1919–29). Increase in pneumonia risk associated with ICS containing medications is a known class effect. The risk/benefit balance of extrafine fixed triple was evaluated by comparing variations in pneumonia and exacerbation events. Methods: Information on moderate/severe exacerbations and confirmed pneumonia was extracted from TRINITY and TRILOGY. A frequency plot was generated considering days in the study versus cumulative number of events. Results: In TRILOGY study, the number of recorded events was 288 exacerbations (rate: 0.448 exacerbations per patient per year) versus 25 pneumonias (rate: 0.039 events per patient per year) with fixed triple and 353 exacerbations (0.565) versus 18 pneumonias (0.029) with Fostair (figure 1A). In TRINITY study, the number of events was 485 exacerbations (0.472) versus 30 pneumonias (0.029) with fixed triple and 569 exacerbations (0.583) versus 20 pneumonias (0.020) with tiotropium (figure 1B). Overall, treatment with fixed triple therapy reduced exacerbations by 65 events compared to Fostair (adjusted rate ratio: 0.773, p=0.005) and by 84 events compared to tiotropium (0.801, p=0.003). No fatal pneumonias occurred in TRILOGY while 5 pneumonias led to death in TRINITY (1 with fixed triple versus 4 with tiotropium). All pneumonias were classified as non-related to treatment. Conclusions: This analysis confirms that, in two independent populations of COPD patients treated with an ICS containing extrafine fixed triple combination, the number of incident pneumonia remains very small compared to that of moderate/severe exacerbations. The benefit observed in reducing the absolute number of exacerbations outweighs the increase observed in absolute number of pneumonias, thus confirming the positive risk benefit balance of extrafine fixed triple in severe/very severe COPD patients. Please refer to page A260 for declarations of interest in relation to abstract P273.